Heterologous Biosynthesis of Five New Class II Bacteriocins From Lactobacillus paracasei CNCM I-5369 With Antagonistic Activity Against Pathogenic Escherichia coli Strains - Belguesmia, Yanath; Bendjeddou, Kamel; Kempf, Isabelle; Boukherroub, Rabah; Drider, Djamel (Frontiers in Microbiology, 2020)
Lactobacillus paracasei CNCM I-5369 isolated from a traditional Algerian dairy product produces extracellular inhibitory substances, namely bacteriocins, which are active against a panel of pathogenic Escherichia coli strains. This activity was observed only at a narrow pH 4.5-5, and resulted to be heat stable and sensitive to the action of proteolytic enzymes, which indicate a proteinaceous nature. This new strain has a genome of 2,752,975 bp, with a 46.6% G+C ratio and contains at least 2,664 coding sequences. The Bagel software analysis identified five open reading frames (ORFs) that are translated to new class II bacteriocin. Each ORF was cloned in frame with a His-tag tail and expressed in Escherichia coli BL21 (DE3) (pLysS) strain. Of note, each fusion protein carrying any of these ORFs at the C or N-terminal position resulted to be active against E. coli 184 strain used as target organism. This manuscript reports the first multi-bacteriocinogenic strain producing five new class II bacteriocins with activity against Gram-negative bacilli (GNB), namely E. coli. Heterologous expression and activity of each new class II bacteriocin were demonstrated.